Khamoush chekhain - Dr akhter khnam (Ferozsons (PVT) LTD Lahore)
"Khamoush Chekhain" delves into the silent struggles and unspoken emotions of its characters, capturing the essence of inner turmoil and the quest for self-expression in a repressive world.